The Role of the Consultant Pharmacist in Pharmacovigilance: Enhancing Medication Safety and Public Health - Innocent, Ode Edward (Darul Yasin Al Sys, 2026)
Pharmacovigilance is essential for ensuring the continued safety and efficacy of pharmaceuticals, particularly in post-marketing settings where adverse drug reactions (ADRs) may emerge beyond controlled clinical trial conditions. In Nigeria, Consultant Pharmacists have become central actors in advancing pharmacovigilance practice. Equipped with advanced qualifications such as the MPharm (Clinical) and FWAPCP, and formally recognized by the National Agency for Food and Drug Administration and Control (NAFDAC) and the Federal Ministry of Health (FMoH), they lead institutional and national efforts in ADR detection, post-marketing surveillance, signal detection, pharmacoepidemiology, risk management, and patient safety. This article examines the evolving role of Consultant Pharmacists as pharmacovigilance leaders, educators, policy influencers, and clinical collaborators. Despite their expanding influence, significant challenges persist, including underreporting, limited digital infrastructure, and gaps in pharmacovigilance education among community members. Strengthening the integration of Consultant Pharmacists into healthcare governance structures is vital for building a resilient, safety-focused pharmaceutical care system. Their contributions are pivotal not only for ensuring regulatory compliance but also for safeguarding public health and enhancing the quality of pharmaceutical care delivery.